2016
DOI: 10.1007/s11440-015-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

A study of the water retention curve of lime-treated London Clay

Abstract: This paper investigates the drying and wetting soil water retention curves (SWRCs) of statically compacted lime-stabilised London Clay specimens. A series of tests were performed using the contact filter paper method, pressure plate apparatus and a suction-controlled triaxial system incorporating the axis translation technique. These investigated the water retention of the soil under different boundary and stress-state conditions and simultaneously determined the volume change in the soil during drying and wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…By analyzing the changes in the water retention curve when the substrate was compacted (Figure 3), it was clear that the pores decreased their size, diminishing the θ s and increasing the air-entry pressure (h b = α −1 ) due to an increase in the capillary forces [37]. These changes in the porous media water retention capacity are consistent with the observations published in the scientific literature [2,15,24,25,46,47]. For instance, in the S2 compacted water retention curve, the h b increased from 17 to 526 cm, while the h b of the S1 substrate increased from 9 to 53 cm.…”
Section: Discussionsupporting
confidence: 84%
“…By analyzing the changes in the water retention curve when the substrate was compacted (Figure 3), it was clear that the pores decreased their size, diminishing the θ s and increasing the air-entry pressure (h b = α −1 ) due to an increase in the capillary forces [37]. These changes in the porous media water retention capacity are consistent with the observations published in the scientific literature [2,15,24,25,46,47]. For instance, in the S2 compacted water retention curve, the h b increased from 17 to 526 cm, while the h b of the S1 substrate increased from 9 to 53 cm.…”
Section: Discussionsupporting
confidence: 84%
“…The drying path of untreated silt is located slightly below the drying path of lime treated and lime-hydraulic binder treated silts. The obtained water retention curves showed that lime and lime-hydraulic binder treatments increased the water retention capacity of silty soils, confirming the previous findings 10/31 by some authors [15,39,40]. This can be connected to the impact of these treatments on the soil micro-structure [16,21,41,42].…”
Section: Water Retention Curvethermal Propertiessupporting
confidence: 87%
“…Many studies were conducted to assess the influence of different factors on the water retention properties of the soil in geotechnical engineering applications. Numerous investigations (e.g., [23][24][25][26]) noted that the void ratio, water content, and stress state of a soil have a strong influence on the SWCC. Standard laboratory equipment based on the axis translation technique, such as the pressure plate, volume extractor, suction-controlled oedometer, modified triaxial apparatuses, and standard tensiometers, are the most common devices used to control or measure matric suction.…”
Section: Methods Used For Determination Of Soil-water Characteristic mentioning
confidence: 99%